Immunocytochemical localization of opsin in the cell membrane of developing rat retinal photoreceptors (The Rockefeller University Press, 1984)
Mature retinal rod photoreceptors sequester opsin in the disk and plasma membranes of the rod outer segment (ROS). Opsin is synthesized in the inner segment and is transferred to the outer segment along the connecting cilium that joins the two compartments. We have investigated early stages of retinal development during which the polarized distribution of opsin is established in the rod photoreceptor cell. Retinas were isolated from newborn rats, 3-21 d old, and incubated with affinity purified biotinyl-sheep anti-bovine opsin followed by avidin- ferritin. At early postnatal ages prior to the development of the ROS, opsin is labeled by antiopsin on the inner segment plasma membrane. At the fifth postnatal day, as ROS formation begins opsin was detected on the connecting cilium plasma membrane. However, the labeling density of the ciliary plasma membrane was not uniform: the proximal cilium was relatively unlabeled in comparison with the distal cilium and the ROS plasma membrane. In nearly mature rat retinas, opsin was no longer detected on the inner segment plasma membrane. A similar polarized distribution of opsin was also observed in adult human rod photoreceptor cells labeled with the same antibodies. These results suggest that some component(s) of the connecting cilium and its plasma membrane may participate in establishing and maintaining the polarized distribution of opsin.